Copper nano material electromagnetic shielding film and preparation method and application thereof

By mixing copper nanosheets and copper nanowires, the problem of oxidation of copper nanosheets in the air is solved, and the stability and electromagnetic shielding performance of copper nanomaterial electromagnetic shielding film are improved. It is suitable for aircraft and aircraft The electromagnetic shielding protective layer reduces the production cost.

CN119320508APending Publication Date: 2025-01-17NANJING UNIV OF AERONAUTICS & ASTRONAUTICS
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411541015.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

In the prior art, there are fewer synthesis processes for copper nanosheets, and the crystal configuration, size and surface morphology control are immature, resulting in their easy oxidation in the air, affecting the electromagnetic shielding performance, and the electromagnetic interference shielding effect is poor.

Method used

The material layer is accumulated by mixing copper nanosheets and copper nanowires, and is evenly dispersed by ultrasonic oscillation and suction filtered onto an organic solvent-resistant microporous filter membrane to remove the organic matter and oxide layer on the surface, and combined with acid solution cleaning and inert gas drying. A copper nanomaterial electromagnetic shielding film with frequency selectivity and good electromagnetic shielding effect was prepared.

Benefits of technology

It has achieved the improvement of the stability and electromagnetic shielding performance of copper nanomaterial films, with frequency selectivity and good flexibility, and is suitable for electromagnetic shielding protective layers for aircraft and aircraft, reducing production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119320508A_ABST
    Figure CN119320508A_ABST
Patent Text Reader

Abstract

The invention discloses a copper nanomaterial electromagnetic shielding film and a preparation method and application thereof. The electromagnetic shielding film comprises a base material, and a material layer formed by mixing and stacking copper nanosheets and copper nanowires is loaded on the base material; the preparation method comprises the following steps: uniformly mixing and dispersing the copper nanosheets and the copper nanowires, carrying out suction filtration, and removing organic matters and oxide layers on the surfaces, so as to obtain the thin film with the electromagnetic shielding performance. And mixing copper nanowires and copper nanowires, and carrying out suction filtration to prepare the copper nanomaterial film. Due to the uniform grid arrangement of the copper nanosheets and the copper nanowires, the electromagnetic shielding film shows certain frequency selectivity, the working frequency band is 8.9-9.6 GHz, and the electromagnetic shielding film has good stability. The achievement is expected to be applied to electromagnetic shielding protection layers of aircrafts, glass windows of military or civil aircrafts, photoelectric cabins of helicopters and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a film material and a preparation method and application thereof, and in particular to a copper nano material electromagnetic shielding film and a preparation method and application thereof. Background Art

[0002] Electromagnetic radiation refers to the phenomenon of electromagnetic waves carrying energy propagating in space. With the rapid development of the electronics industry, electromagnetic waves are used as carriers of modern communication information. The impact of a large amount of electromagnetic interference and radiation on highly sensitive electronic devices and human health cannot be underestimated.

[0003] In current research, traditional strategies to address electromagnetic interference (EMI) rely on various materials to separate the target from the source of electromagnetic waves through different reflection or absorption mechanisms. Specific materials with conductivity or magnetism, that is, electromagnetic wave interaction, can achieve the effect of reducing EMI by absorbing electromagnetic waves. Among them, the most widely used and cost-effective EMI shielding materials are conductive materials, such as metal-based films, metal foils, and meshes. The micro- or nano-structure of the internal structure of the shielding film is also a way to improve the EMI shielding efficiency (SE). The cavities and pores inside the microstructure will reflect electromagnetic waves multiple times. This method usually causes multiple internal reflections by maximizing the movement path of electromagnetic waves (EM) in the shielding system, thereby enhancing the EMI shielding effect.

[0004] Among the three nanostructures of gold, silver and copper with excellent plasmon properties, the research on gold and silver nanostructures and copper nanowires is relatively mature, while the research on copper nanosheets is less and mainly focuses on copper sulfide nanosheets.

[0005] At present, there are relatively few synthesis processes for copper nanosheets, and the technology for controlling their crystal configuration, radial size, length and surface morphology is still immature. In addition, the chemical properties of pure copper nanosheets are relatively active, and they are easily oxidized and corroded when exposed to air, which interferes with subsequent performance testing and applications, resulting in certain limitations in the use of the resulting products. Summary of the invention

[0006] Purpose of the invention: The purpose of the present invention is to provide a copper nanomaterial electromagnetic shielding film with frequency selectivity and good electromagnetic shielding effect;

[0007] The second object of the present invention is to provide a method for preparing the above copper nanomaterial electromagnetic shielding film;

[0008] The third object of the present invention is to provide the application of the above copper nanomaterial electromagnetic shielding film.

[0009] Technical solution: The copper nanomaterial electromagnetic shielding film described in the present invention includes a substrate, on which is loaded a material layer formed by mixed stacking of copper nanosheets and copper nanowires.

[0010] The copper nanosheets have a size of 1 μm-9 μm and a triangular or hexagonal shape. Larger-sized copper nanosheets are stacked to improve the electromagnetic shielding performance of the entire system.

[0011] The copper nanowire has a diameter of 40-60 nm and a length of 13-25 nm. The copper nanowire serves as a medium for connecting copper nanosheets to improve the conductivity of the entire system.

[0012] Wherein, the substrate is at least one microporous filter membrane resistant to organic solvents; preferably a PET membrane.

[0013] The method for preparing the copper nanomaterial electromagnetic shielding film comprises uniformly mixing and dispersing the copper nanosheets and the copper nanowires, filtering and removing the organic matter and the oxide layer on the surface, and obtaining a film with electromagnetic shielding performance.

[0014] The following steps are included:

[0015] (1) purifying, mixing and dispersing the copper nanowires and copper nanosheets, and obtaining a uniformly dispersed solution by ultrasonic vibration;

[0016] (2) filtering the solution obtained in step (1) onto a microporous filter membrane resistant to organic solvents, and transferring it onto a substrate under pressure to obtain a copper nanomaterial film;

[0017] (3) The film obtained in step (2) is placed in an acid solution for cleaning, and then purged and dried with an inert gas to obtain a copper nanomaterial electromagnetic shielding film.

[0018] Wherein, the concentration of copper nanosheets in step (1) is 80mg / L-100mg / L, and the concentration of copper nanowires is 40mg / L-60mg / L. The copper nanosheets and copper nanowires are mixed in a volume ratio of 1:1-2:1. When the ratio is less than the aforementioned range, there will be too few connections between the copper nanomaterials, resulting in excessive film resistance, thereby affecting the electromagnetic shielding performance; when the ratio is greater than the aforementioned range, the subsequent residual organic matter and the oxide layer on the surface cannot be completely removed, increasing the resistance and affecting the actual performance.

[0019] Wherein, in step (1), the copper nanosheets are prepared by the following steps: copper salt, hydrophilic surfactant, hydrophobic surfactant and reducing agent are dissolved in water, alkali metal halide solution is added, the obtained mixed solution is first reacted at 100-110°C for 5-6h, then quickly cooled to 80-90°C and continued to be sealed and heated for 5-6h to obtain micron-sized copper nanosheets.

[0020] Wherein, the molar ratio of the copper salt, the hydrophobic surfactant, the hydrophilic surfactant and the reducing agent is 1:0.25-0.4:0.125-0.2:2.

[0021] Among them, the hydrophilic surfactant is polyvinyl pyrrolidone, referred to as PVP; the hydrophobic surfactant is hexadecylamine, referred to as HDA; the alkali metal halide is at least one of KI, NaI or NaBr; and the reducing agent is preferably glucose.

[0022] Wherein, in step (2), the filtration time is 30-35s. If the filtration time is too short, more solvent will remain. If the filtration time is too long, the copper nanomaterial will stick to the filter membrane, which is not conducive to the subsequent transfer operation. The organic solvent-resistant microporous filter membrane is preferably an acetic acid filter membrane.

[0023] Wherein, in step (2), the pressurization pressure is 0.8-1 MPa. Too low a pressure will result in incomplete transfer, while too high a pressure will cause the acetic acid filter membrane to rupture and affect the transfer effect. The pressurization time is 50-60 s.

[0024] Wherein, in step (3), the acidic solution is a weak acid solution such as acetic acid, and the solution concentration is 80-90%.

[0025] Wherein, in step (3), the inert gas is preferably nitrogen.

[0026] The copper nanomaterial electromagnetic shielding film is used in the electromagnetic shielding protective layer of aircraft, the glass windows of military or civil aircraft, and the optoelectronic cockpit of helicopters.

[0027] Invention principle: When preparing copper nanosheets, hydrophilic and hydrophobic surfactants selectively block the (200) planes on both sides of the Cu nanowires, allowing the nanowires to <111> The halogen ions can replace the surfactants on Cu(200) and Cu(111), accelerating the growth of <100> The growth rate of the Cu nanoclusters in the (111) direction is increased, and the growth rate of the Cu nanoclusters on the (111) surface is decreased, so that the Cu nanoclusters grow into a flat plate. The use of hydrophilic and hydrophobic surfactants makes the entire preparation process hydrophilic.

[0028] The present invention uses copper nanosheets with larger sizes and copper nanowires with higher aspect ratio as the materials of electromagnetic shielding film. The electromagnetic shielding performance of electromagnetic shielding materials, especially polymer composite materials, is affected by many factors. The main influencing factors include electrical properties and magnetic properties. The higher the conductivity, the higher the reflection loss (SER) and absorption loss (SEA), which proves that the conductivity has a positive effect on the reflection and absorption of electromagnetic waves. The larger the aspect ratio of the nanowire and the diameter-to-thickness ratio of the nanosheet, the better the electromagnetic shielding effect of the composite material.

[0029] Beneficial effects: Compared with the prior art, the present invention achieves the following significant effects:

[0030] (1) Copper nanosheets with larger sizes and copper nanowires with higher aspect ratios are used as the materials for electromagnetic shielding films. Due to the uniform grid arrangement of copper nanosheets and copper nanowires, the electromagnetic shielding film exhibits certain frequency selectivity, has an operating frequency band of 8.9-9.6 GHz, and has good stability. (2) The present invention provides a method for preparing copper nanosheets by an aqueous phase method, which prepares copper nanosheets with a size range of 1 μm-9 μm. The prepared copper nanosheets have a stability of six months in solution. (3) The copper nanomaterial film of the present invention has good electromagnetic shielding performance and can be bent as a flexible material. It is a potential electromagnetic shielding material. (4) In terms of frequency selectivity, compared with general frequency selective surfaces, the nanomaterial film has better flexibility and thinner thickness. The frequency selectivity brought by the structure of the material itself reduces the production cost. (5) The material of the present invention can be applied to aircraft electromagnetic shielding protective layers, glass windows of military or civilian aircraft, and helicopter optoelectronic cockpits. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 are scanning electron microscope and transmission electron microscope images of the copper nanosheets prepared in Example 1;

[0032] Figure 2 is the XRD pattern of the copper nanosheet prepared in Example 1;

[0033] Figure 3 This is a physical picture of the copper nanomaterial film prepared in Example 1;

[0034] Figure 4 is a scanning electron microscope image of the copper nanomaterial film prepared in Example 1;

[0035] Figure 5 This is a diagram showing the electromagnetic shielding effect of the copper nanomaterial film prepared in Example 1;

[0036] Figure 6 This is a diagram showing the electromagnetic shielding effect of thin films prepared using the copper nanosheets and copper nanowires in Example 1;

[0037] Figure 7 is a scanning electron microscope image of the copper nanosheet prepared in Comparative Example 2;

[0038] Figure 8 This is a diagram showing the electromagnetic shielding effect of the copper nanomaterial film prepared in comparative example 3. DETAILED DESCRIPTION

[0039] The present invention is described in further detail below.

[0040] Example 1

[0041] A method for preparing a copper nanosheet material electromagnetic shielding film comprises the following steps:

[0042] Step 1: Preparation of copper nanosheets

[0043] 126mgCuCl2·2H2O, 73.2mgHDA, 1.2g PVP with a relative molecular mass of 8000, and 300mg glucose were added to 20mL deionized water, and then 490μL of 0.01mol / L KI solution was added. The resulting mixed solution was reacted in an oil bath at 100℃ for 6h, then quickly cooled to 80℃ and continued to be sealed and heated for 6h to obtain micron-sized copper nanosheets. TEM and SEM images of copper nanosheets are shown in Figure 1. Figure 1 As shown in (a) and (b) in the figure, the XRD pattern is as follows Figure 2 shown.

[0044] Step 2: Preparation of copper nanowires

[0045] 0.042 g CuCl2·2H2O, 0.36 g HDA, and 0.1 g glucose were added to 20 ml deionized water, stirred and heated at 110°C and 400 rpm for 6 h, washed, centrifuged, and purified with n-hexane to obtain the desired copper nanowires.

[0046] Step 3: Preparation of copper nanomaterials

[0047] Acetone was added to the sample obtained in step 1, and after preliminary cleaning by centrifugation at 8000 rpm for 10 min, the supernatant was discarded, and the precipitate was dispersed in toluene, and the concentration of copper nanosheets was 80 mg / L; acetone was added to the sample obtained in step 2, and after preliminary cleaning by centrifugation at 6000 rpm for 10 min, the supernatant was discarded, and the precipitate was dispersed in toluene, and the concentration of copper nanowires was 40 mg / L; then the two toluene dispersions were mixed in a volume ratio of 1:1, and oscillated at 100 rpm in an oscillator at room temperature to obtain uniformly dispersed copper nanomaterials.

[0048] Step 4: Obtaining a copper nanomaterial film on a PET film

[0049] Place the acetic acid filter membrane in the center of the filtration equipment, soak it with toluene, remove the bubbles, pour in the copper nanomaterial in step 3, and filter for 30 seconds. Take a piece of 5×5cm 2 Take a PET film of different size, remove the protective film on the front side, stick the side with the filtration material to the front side of the PET film, pressurize it at 1 MPa for 1 minute, peel off the acetic acid filter membrane, and obtain the copper nanomaterial film transferred to the PET film.

[0050] Step 5: Preparation of copper nanomaterial film

[0051] The transferred copper nanomaterial film is placed in an acetic acid solution with a concentration of 80% for cleaning for 10-15 seconds. After cleaning, it is placed in deionized water to remove residual acetic acid. The surface is purged with nitrogen to dry it. The copper nanomaterial film with electromagnetic shielding effect is obtained. The actual picture is as follows Figure 3 shown.

[0052] Depend on Figure 4 The scanning electron microscope image shows the structure of the obtained copper nanomaterial film.

[0053] The electromagnetic shielding effect was tested and the results were as follows Figure 5 As shown. Figure 6 In comparison, there is an additional absorption effect at 8.9-9.6 GHz, showing frequency selectivity.

[0054] Example 2

[0055] A method for preparing a copper nanosheet material electromagnetic shielding film comprises the following steps:

[0056] Step 1: Preparation of copper nanosheets

[0057] 126 mg CuCl2·2H2O, 73.2 mg HDA, 0.8 g PVP with a relative molecular mass of 8000, and 300 mg glucose were added to 20 mL deionized water, and then 490 μL of 0.01 mol / L NaI solution was added. The obtained mixed solution was reacted in an oil bath at 110°C for 5 h, and then quickly cooled to 80°C and continued to be sealed and heated for 6 h to obtain micron-sized copper nanosheets.

[0058] Step 2: Preparation of copper nanowires

[0059] 0.042 g CuCl2·2H2O, 0.36 g HDA and 0.1 g glucose were added to 20 ml deionized water, stirred and heated at 110°C and 400 rpm for 6 h, washed, centrifuged and purified with n-hexane to obtain the desired copper nanowires.

[0060] Step 3: Preparation of copper nanomaterials

[0061] Acetone was added to the sample obtained in step 1, and after preliminary cleaning by centrifugation at 8000 rpm for 10 min, the supernatant was discarded, and the precipitate was dispersed in toluene, and the concentration of copper nanosheets was 80 mg / L; acetone was added to the sample obtained in step 2, and after preliminary cleaning by centrifugation at 6000 rpm for 10 min, the supernatant was discarded, and the precipitate was dispersed in toluene, and the concentration of copper nanowires was 40 mg / L; then the two toluene dispersions were mixed at a volume ratio of 1.5:1, and oscillated at 100 rpm in an oscillator at room temperature to obtain uniformly dispersed copper nanomaterials.

[0062] Step 4: Obtaining a copper nanomaterial film on a PET film

[0063] Place the acetic acid filter membrane in the center of the filtration equipment, soak it with toluene, remove the bubbles, pour in the copper nanomaterial in step 3, and filter for 30 seconds. Take a piece of 5×5cm 2 Take a PET film of different size, remove the protective film on the front side, stick the side with the filtration material to the front side of the PET film, pressurize it at 0.9 MPa for 1 minute, peel off the acetic acid filter membrane, and obtain the copper nanomaterial film transferred to the PET film.

[0064] Step 5: Preparation of copper nanomaterial film

[0065] The transferred copper nanomaterial film is placed in an acetic acid solution with a concentration of 80% for cleaning for 10-15 seconds. After cleaning, it is placed in deionized water to remove residual acetic acid, and the surface is purged with nitrogen to dry it, thereby obtaining a copper nanomaterial film with electromagnetic shielding effect.

[0066] Example 3

[0067] A method for preparing a copper nanosheet material electromagnetic shielding film comprises the following steps:

[0068] Step 1: Preparation of copper nanosheets

[0069] 126 mg CuCl2·2H2O, 48.8 mg HDA, 1.2 g PVP with a relative molecular mass of 8000, and 300 mg glucose were added to 20 mL deionized water, and then 490 μL of 0.01 mol / L NaBr solution was added. The obtained mixed solution was reacted in an oil bath at 110°C for 5 h, and then quickly cooled to 90°C and continued to be sealed and heated for 5 h to obtain micron-sized copper nanosheets.

[0070] Step 2: Preparation of copper nanowires

[0071] 0.042 g CuCl2·2H2O, 0.36 g HDA and 0.1 g glucose were added to 20 ml deionized water, stirred and heated at 110°C and 400 rpm for 6 h, washed, centrifuged and purified with n-hexane to obtain the desired copper nanowires.

[0072] Step 3: Preparation of copper nanomaterials

[0073] Acetone was added to the sample obtained in step 1, and after preliminary cleaning by centrifugation at 8000 rpm for 10 min, the supernatant was discarded, and the precipitate was dispersed in toluene, and the concentration of copper nanosheets was 80 mg / L; acetone was added to the sample obtained in step 2, and after preliminary cleaning by centrifugation at 6000 rpm for 10 min, the supernatant was discarded, and the precipitate was dispersed in toluene, and the concentration of copper nanowires was 40 mg / L; then the two toluene dispersions were mixed in a volume ratio of 2:1, and oscillated at 100 rpm in an oscillator at room temperature to obtain uniformly dispersed copper nanomaterials.

[0074] Step 4: Obtaining a copper nanomaterial film on a PET film

[0075] Place the acetic acid filter membrane in the center of the filtration equipment, soak it with toluene, remove the bubbles, pour in the copper nanomaterial in step 3, and filter for 30 seconds. Take a piece of 5×5cm 2 Take a PET film of different size, remove the protective film on the front side, stick the side with the filtration material to the front side of the PET film, pressurize it at 0.8 MPa for 1 minute, peel off the acetic acid filter membrane, and obtain the copper nanomaterial film transferred to the PET film.

[0076] Step 5: Preparation of copper nanomaterial film

[0077] The transferred copper nanomaterial film is placed in an acetic acid solution with a concentration of 80% for cleaning for 10-15 seconds. After cleaning, it is placed in deionized water to remove residual acetic acid, and the surface is purged with nitrogen to dry it, thereby obtaining a copper nanomaterial film with electromagnetic shielding effect.

[0078] Comparative Example 1

[0079] Compared with Example 1, the only difference is that the copper nanosheets prepared by the method mentioned in the paper Sun Y, Xu L, Yin Z, et al. Synthes is of copper submicro / nanoplates with high stability and their recyclable superio rcatalytic activity towards 4-nitrophenol reduction [J]. Journal of Materials Chemistry A, 2013, 1(39): 12361. DOI: 10.1039 / c3ta12526b. have an average edge length of about 180-280 nm and a thickness of 8 nm.

[0080] Comparative Example 2

[0081] Compared with Example 1, the only difference is that the copper nanosheets are heated at 110°C for 12 hours, and the obtained product is Figure 7 As shown in the figure, it can be seen that the obtained copper nanosheets have low purity and contain many copper nanoparticles.

[0082] Comparative Example 3

[0083] Compared with Example 1, the only difference is that the volume ratio of the nanosheets to the nanowires is 0.8, and the electromagnetic shielding effect of the obtained copper nanomaterial film is as follows: Figure 8 As shown in the figure, it can be seen that the overall electromagnetic shielding effect is poor, because there are fewer connections between copper nanomaterials and the overall resistance is large.

Claims

1. A copper nanomaterial electromagnetic shielding film, characterized in that: The invention comprises a substrate, on which a material layer formed by mixing and stacking copper nanosheets and copper nanowires is loaded.

2. The copper nanomaterial electromagnetic shielding film according to claim 1, characterized in that: The copper nanosheet has a size of 1 μm-9 μm; the copper nanowire has a diameter of 40-60 nm and a length of 13-25 nm.

3. A method for preparing the copper nanomaterial electromagnetic shielding film according to claim 1, characterized in that: The copper nanosheets and copper nanowires are uniformly mixed and dispersed, and the organic matter and oxide layer on the surface are filtered and removed to obtain a film with electromagnetic shielding performance.

4. The method for preparing the copper nanomaterial electromagnetic shielding film according to claim 3, characterized in that: The following steps are involved: (1) purifying, mixing and dispersing the copper nanowires and copper nanosheets, and obtaining a uniformly dispersed solution by ultrasonic vibration; (2) filtering the solution obtained in step (1) onto a microporous filter membrane resistant to organic solvents, and then transferring it onto a substrate under pressure to obtain a copper nanomaterial film; (3) The film obtained in step (2) is placed in an acid solution for cleaning, and then purged and dried with an inert gas to obtain a copper nanomaterial electromagnetic shielding film.

5. The method for preparing the copper nanomaterial electromagnetic shielding film according to claim 4, characterized in that: In step (1), the volume ratio of copper nanosheets to copper nanowires is 1:1-1:

2.

6. The method for preparing the copper nanomaterial electromagnetic shielding film according to claim 4, characterized in that: In step (1), the copper nanosheets are prepared by the following steps: copper salt, hydrophilic surfactant, hydrophobic surfactant and reducing agent are dissolved in water, alkali metal halide solution is added, the obtained mixed solution is first reacted at 100-110° C. for 5-6 hours, then quickly cooled to 80-90° C. and continued to be sealed and heated for 5-6 hours to obtain micron-sized copper nanosheets.

7. The method for preparing the copper nanomaterial electromagnetic shielding film according to claim 6, characterized in that: The molar ratio of the copper salt, the hydrophobic surfactant, the hydrophilic surfactant and the reducing agent is 1:0.25-0.4:0.125-0.2:

2.

8. The method for preparing the copper nanomaterial electromagnetic shielding film according to claim 6, characterized in that: The hydrophilic surfactant is polyvinyl pyrrolidone, the hydrophobic surfactant is hexadecylamine, and the alkali metal halide is at least one of KI, NaI or NaBr.

9. The method for preparing the copper nanomaterial electromagnetic shielding film according to claim 4, characterized in that: In step (1), the concentration of copper nanosheets is 80-100 mg / L; the concentration of copper nanowires is 40-60 mg / L.

10. Use of the copper nanomaterial electromagnetic shielding film according to claim 1 in an aircraft electromagnetic shielding protective layer, a glass window of a military or civil aircraft, and a helicopter optoelectronic cockpit.